New sesquiterpeniod esters form Blumea balsamifera (L.) DC. and their anti-influenza virus activity. Issue 5 (4th March 2022) - Xiong, Yan; Yi, Ping; Li, Yuhuan; Gao, Rongmei; Chen, Junlei; Hu, Zhanxing; Lou, Huayong; Du, Caixia; Zhang, Jiayu; Zhang, Yu; Yuan, Chunmao; Huang, Liejun; et al.
Abstract: Phytochemical studies led to the isolation of five new sesquiterpeniod esters, named balsamiferine N-R, along with ten known compounds (6-15) from the leaves of Blumea balsamifera (L.) DC. The skeletons of nine known sesquiterpeniods belong to guaiane and eudesmane. The structures of the new compounds including their absolute configurations were elucidated by comprehensive spectroscopic analysis, and quantum-chemical electronic circular dichroism (ECD) calculation. Compounds 3 and 4 showed significant inhibitory effects on influenza A virus (H3N2) with IC50 values of 46.23 μg/mL and 38.49 μg/mL, respectively. It was the first report on the anti-influenza A virus constituents from B. balsamifera . Graphical Abstract: UF0001